Assessing social work and nursing students' intentions to work with dying patients. Issue 1 (2nd January 2018) - Shinan-Altman, Shiri
Abstract: This study assessed social work and nursing students' intentions to provide end-of-life care, based on the Theory of Planned Behavior. A total of 181 social work and nursing students completed a questionnaire examining intentions to provide end-of-life care, attitudes, subjective norms, perceived control, death anxiety, subjective knowledge, and sociodemographic characteristics. Students manifested a moderate level of intentions to provide end-of-life care, with nursing students indicating higher levels of intentions than social work students. Multiple regression analyses revealed that attitudes, subjective norms, and previous experience were the main predictors of intentions to provide end-of-life care. Recommendations for academic programs are discussed.